Customer’s Orientation, Show-rooming Behavior, and Sales Performance: Mediated Moderation Model of Taiwan's Services Industry - Hung-Xin Li (Journal of Management Practices, Humanities and Social Sciences, 2024)
This study's main objective is to evaluate the impact of growing market rivalry on managers at Taiwan's Telkom Corporation who work in the services sales division. The purpose of the study of the study includes examining how these managers impact customer orientation and customer showrooming behavior as investigating the role of firm innovativeness as a mediator. In addition, the investigation also focuses on determining the effect of supervisors' psychological service climate as a moderator variable on the relationship between these two variables and their collective impact on sales performance. A total of 300 customer front-line employees from Taiwan's Telkom Company who were engaged in service sales formed our sample; we analyzed their data with structural equation modelling to examine this area. It is also possible that some other variables affect these two main determinants, so further research is needed to understand how they collectively influence sales success. The results show that both customer showrooming behavior and customer orientation have a positive impact on sales performance. In addition, showrooming behavior, client orientation, and sales performance can be influenced by business innovativeness. Additionally, it shows how the supervisor's psychological service climate positively mediates the relationship between business innovativeness and sales success. The investigation of this study suggests that professionals in the services industry can derive two lessons, which are on showrooming behaviour management and client orientation promotion. Based on the findings, it has been shown that business innovation is a very important contributing factor towards improved sales performance. In addition, understanding how employees feel about their boss's psychological service environment is important for enhancing organizational practices. Many research opportunities can be undertaken in the future, which would involve various types of organizations and large samples from industries, even though the present study contributes substantially. Future research should, it is suggested, concentrate on particular facets of corporate innovation while also taking relationship length and consumer loyalty into account. Longitudinal research can also shed light on the changing trends in the services sector.